2009
DOI: 10.3390/ijms10031081
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protection Against Free Radicals: A Case for Multiple Testing to Establish Structure-activity Relationships for Antioxidant Potential of Anthocyanic Plant Species

Abstract: DNA damage by reactive species is associated with susceptibility to chronic human degenerative disorders. Anthocyanins are naturally occurring antioxidants, that may prevent or reverse such damage. There is considerable interest in anthocyanic food plants as good dietary sources, with the potential for reducing susceptibility to chronic disease. While structure-activity relationships have provided guidelines on molecular structure in relation to free hydroxyl-radical scavenging, this may not cover the situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 39 publications
(39 reference statements)
1
19
1
Order By: Relevance
“…Their observations indicated that the red cabbage extracts might not engage in antioxidative protection against H 2 O 2 action, and might instead behave as pro-oxidants. Contrary to the results of Philpott et al [46], we found the ATH extract from red cabbage demonstrated antioxidative properties and partly protected blood plasma proteins, as well as lipids, against H 2 O 2 -induced damage. To exclude the possibility of direct interactions between ATH extract and plasma components, control experiments using blood plasma and the tested extract only (no addition of ONOO -or H 2 O 2 ) were performed; no pro-oxidative effects of the tested ATH were found (data not presented).…”
Section: Disscusioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Their observations indicated that the red cabbage extracts might not engage in antioxidative protection against H 2 O 2 action, and might instead behave as pro-oxidants. Contrary to the results of Philpott et al [46], we found the ATH extract from red cabbage demonstrated antioxidative properties and partly protected blood plasma proteins, as well as lipids, against H 2 O 2 -induced damage. To exclude the possibility of direct interactions between ATH extract and plasma components, control experiments using blood plasma and the tested extract only (no addition of ONOO -or H 2 O 2 ) were performed; no pro-oxidative effects of the tested ATH were found (data not presented).…”
Section: Disscusioncontrasting
confidence: 56%
“…Philpott et al [46] underlined the dangers of generalizing to potential health benefits based solely on identification of high ATH content in plants, or other similar approaches. Their observations indicated that the red cabbage extracts might not engage in antioxidative protection against H 2 O 2 action, and might instead behave as pro-oxidants.…”
Section: Disscusionmentioning
confidence: 99%
“…Kumara was by far the most important vegetable in the Maori diet in early New Zealand and is still widely eaten today. There are a number of chemical constituents of the tubers that could be protective (20,25,26). Although only 1% of the chemical constituents are protein, nevertheless these proteins may have some important properties.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous dietary antioxidants interact with endogenous antioxidants to form a cooperative network of cellular antioxidants, including free radical scavengers. A range of cell types also contain enzymatic cellular defence mechanisms to eliminate free radicals, including inhibitors of pro-oxidant enzymes, and inducers of endogenous defences (14,48,49). All of these classes of agents may be considered anti-mutagens.…”
Section: Examples Of Anti-mutagen Protection Against Dišerent Classesmentioning
confidence: 99%
“…For example, we considered a range of diŠerent red-purple coloured vegetables in the New Zealand diet, to show very potent antioxidant properties, occurring through various mechanisms (49,59). Some of these pigments are contained in the vacuole of a cell, where they will be readily available when the food plat is masticated.…”
Section: Examples Of Anti-mutagen Protection Against Dišerent Classesmentioning
confidence: 99%